Prevalencia de parásitos gastrointestinales en caninos de la ciudad de Pasaje - Márquez Gallardo, Normandie Madeleine (2014)
The present research on gastrointestinal parasites in dogs was held out in the town of Pasaje, based on the following objectives: 1) Establish the prevalence of gastrointestinal parasites in dogs of the urban parishes of the city of Pasaje, 2) To determine the prevalence of gastrointestinal parasites in dogs according to their area of origin, race, sex, age, type of food and hábitat 3) Develop an epidemiological map of the canton Pasaje. In addition the prevalence was determined the gender of parasite, fieldwork methodology consisted of dividing areas (parroquias) to the Pasaje to take stool samples in 200 apparently healthy animals, which were analyzed at the laboratory of Parasitology of the Universidad Técnica de Machala to determine the variables. After the respective analysis and tabulation of the data could be obtained, the prevalence of intestinal parasites in dogs from the city of Pasaje, of the 200 animals evaluated, 121 turned to be positive to gastrointestinal parasites, giving a percentage infection of 60.5%. According to the source the highest percentage was found in Loma de Franco parish and Tres Cerritos 74.2%, depending on the size of the race the highest number obtained it in the big with 67.3% size and the lowest in medium-sized 55.8%. Female dogs were 61.0% compared to males who obtained 60.0%, under 6 months had a 64.9%. Youth doors home habitat animals had a 71.8% being one higher percentage.In this way concluded that animals evaluated to determine prevalence of gastrointestinal parasites in case of the Ancylostoma caninum found a 35% while that Ajila (2012) found a 13% and Apolo (2007) 23.6% both investigations were held Machala, lower prevalence that may be due to the influence of the veterinarian in control of parasitic diseases in domestic animals in this city.